Analisis Perbedaan Tingkat Kebugaran Jasmani Siswa SMK Bahrul Ulum dan MAN Kota Surabaya - Muhammad Nauval Zahy Latief; Nur Ahmad Arief (MAN Insan Cendekia Jambi, 2026)
This research aims to find out the comparison between the physical fitness level of MAN Surabaya students and SMK Bahrul Ulum. This type of research is non-experimental with comparative design. The sample used was students from classes X and XI at MAN Surabaya and SMK Bahrul Ulum which totaled 128 students. Data collection using the PACER test. Data analysis applies descriptive statistics and t-tests. The findings of the study were a significance value of 0.000 < 0.05. The average VO2max value at MAN Surabaya is 1.22 while SMK Bahrul Ulum is 1.00 which means that MAN Surabaya has a better level of physical fitness than SMK Bahrul Ulum. The conclusion of this study is that there is a difference between the level of physical fitness of MAN Surabaya students and SMK Bahrul Ulum.